Budaya Ngopi Masyarakat Kota Santri Jombang - Neni Dwi Lestari; Yudiana Indriastuti (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
Coffee or coffee is a rich activity of individuals, from young to old, from student to employee. Nowadays coffee or coffee activities have developed a sense of meaning in the cultural context. The type of research used is qualitative descriptive by applying methods of data collection through in-depth interviews, observations, and documentation. Data analysis techniques include data collection, presentation, data reduction, and deduction drawing. The purpose of this study is to understand and understand the perceptions of the coffee culture by the people of the town of santri jombang. The result of this study is that the senior citizens of the jombang are aware of the cultural coffee culture of ancient times, where the coffee culture undergoes development and has a wide range of meaning for each individual, from the coffee culture to the need of each individual as a social being, as a means of entertainment, and so on. While the coffee culture has undergone social development and changes, it is essentially the same goal for each individual to interact with another person to shed all feelings experienced, even though the meaning of coffee is to drink coffee, not all of them buy coffee, can even be non-coffee. They are simply looking for a comfortable place to have a relaxed, free chat. Talking helps to blow things up. Keywords: Coffee culture, perception, social communication, social change